The effect of the association of watermelon (Citrullus lana tus) with corn (Zea mays) on the population and damage caused by three insects pests and the yield of those crops in Ciénaga Grande de Lorica, Córdoba - DEL C. BANDA S., LAGUANDIO; CORREDOR-P., DARÍO; CORREDOR-S., GUILLERMO (Revista Colombiana de Entomología, 2004)
In order to understand the effect of the association of watermelon [Citrillus lanatus (Thumb) Matsum &:. Nakai] with corn (Zea mays L.), on Diabrotica balteata Lec. and Aphis gossypii Glover in watermelon. on Spodoptera frugiperda Smith and D. balteata in corn. and yields in the Ciénaga Grande de Lorica (Córdoba - Colombia). three associations were evaluated with watermelon (4.800 plants per hectare) with corn ( 10.000, 20.000 and 30.000 plants per hectare) and their respective monocultures. during the first semester of 2000. The experimental design used was a complete randomized block. Populations and the damage of the insects. yields. quality of the watermelon. profitability and the land equivalent ratio (ler) were quantified. Results showed statistically significance reduction in the population and damage of D. balteata and A. gossypii in associated watermelon with respect to the monoculture. In corn the incidence of S. frugiperda was less in 10.000 plants per hectare and statistical differences between treatments were not detected for D. balteata. The best yield and quality of watermelon were obtained in association with 10.000 corn plants per hectare: 21.94 l kg/ha; and the least with 30.000 corn plants per hectare: 6.800 kg/ha; in the monoculture yield was 20.460 kg/ha. Corn yield varied between 1.280 and 2.813 kg/ha, proportional to the density of plants. Economically, the best treatment was watermelon with corn at the lowest density. with the highest index of 3, 1 and a ler of 1.55; this was favored by a smaller population and incidence of the insects pests studied with a preference for monoculture over associated systems.